2006
DOI: 10.1139/i06-074
|View full text |Cite
|
Sign up to set email alerts
|

Optic neuropathy in refractory neurosarcoidosis treated with TNF-α antagonist

Abstract: Corticosteroids alone and with immunosuppressive agents failed to suppress the active disease. Alternative therapy of infliximab perfusions resulted in disease remission and relative visual improvement, and this treatment may warrant further clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…26 Similarly, in many other types of retinal disease, increased levels of TNF are associated with increased retinal degeneration. Because of this, TNF inhibitory antibodies (infliximab, etanercept) have been developed and are being used in trials to treat human diseases such as agerelated macular degeneration, 27 Eales disease, 28 neurosarcoidosis, 29 various forms of ocular inflammation, 30 diffuse subretinal fibrosis syndrome, 31 and glaucoma. 32 As has been noted 33 and as our present study underscores, there are instances in which TNF plays a poorly understood protective role in retinal degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…26 Similarly, in many other types of retinal disease, increased levels of TNF are associated with increased retinal degeneration. Because of this, TNF inhibitory antibodies (infliximab, etanercept) have been developed and are being used in trials to treat human diseases such as agerelated macular degeneration, 27 Eales disease, 28 neurosarcoidosis, 29 various forms of ocular inflammation, 30 diffuse subretinal fibrosis syndrome, 31 and glaucoma. 32 As has been noted 33 and as our present study underscores, there are instances in which TNF plays a poorly understood protective role in retinal degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-tumor necrosis factor (TNF) agent infliximab has been successfully prescribed for the treatment of some cases of refractory disease. 35,36 However, infliximab has also been associated with subsequent development of optic neuritis. 37,38 Orbital Disease Ocular sarcoidosis can also affect the adnexa and the orbit.…”
Section: Figurementioning
confidence: 99%
“…Mycophenolate mofetil, previously used in systemic sarcoidosis, has been efficacious and well tolerated in neurosarcoidosis [98,99]. Disease remission in refractory neuro-ophthalmic sarcoidosis with TNF-a inhibitors, thalidomide and infliximab, has also been reported [100][101][102][103]. Salama et al [103] reported successful remission with infliximab in a case of sarcoid optic neuropathy, refractory to corticosteroid, azathioprine and methotrexate, in which the patient had vision recovery.…”
Section: Managementmentioning
confidence: 99%